Replacement of Avulsed Tooth in the Esthetic Zone Using Chair-side Fabricated Resin Composite Pontic: A Case Report - Sufyan Nisar Ahmed Ansari; AbdulAziz Osama Al Qahtani (Bahrain Medical Society, 2024)
Avulsion of permanent teeth is a complex traumatic dental injury (TDI) where a tooth is completely displaced out of its socket without fracturing. The resultant esthetic and functional compromises are distressing for the patient and require immediate attention. The emergency management of an avulsed permanent tooth is to replant it in its socket or preserve it in suitable storage media (saliva, milk, Hanks' Balanced Salt Solution) within 60 minutes of injury. However, if the tooth is lost or is not replanted within 60 minutes, alternative methods to address the patient's esthetic concerns must be sought. This case report describes the replacement of a lost avulsed permanent tooth with a chairside fabricated resin composite pontic and a 6-month follow-up period. Keywords: Artificial tooth; Immediate partial denture; Resin-bonded fixed partial denture; Temporary dental restoration; Fibre-reinforced bridge